Analisis Korelasi Pernikahan Dini dengan Angka Perceraian di Kabupaten Sumenep - Hariri, Achmad; Ichda Wahyuni, Holy (Humanis, 2025)
This study aims to analyze the correlation between early marriage and the divorce rate in Sumenep Regency. The phenomenon of early marriage has become a significant social issue in this region and is estimated to contribute to the high divorce rate. This research uses a qualitative approach. Data were collected through surveys and literature reviews that examined reports from relevant institutions, as well as in-depth interviews with divorced couples. The findings show a significant positive correlation between early marriage and the divorce rate in Sumenep Regency. The younger the marriage age, the higher the likelihood of divorce, due to a lack of mental, emotional, and financial preparedness of the couple. Furthermore, early marriage is often followed by immaturity in understanding marital commitment, which increases the risk of problems. Although early marriage is not a direct cause of divorce, the emotional and psychological unpreparedness of the couple is an important factor that increases the risk of divorce.